Antimicrobial Resistance in the Environment. - Keen, Patricia L.; Montforts, M. H. M. M. (Mark H. M. M.) (Chicester : John Wiley & Sons, 2012)
This book explores the role that environmental distribution of antimicrobial resistance genes and antibiotics plays in ecosystem and human health. The text features a multi-disciplinary framework that connects microbiology, environmental toxicology, and chemistry to assess human and ecological risk associated with exposure to antibiotics or antibiotic resistance genes as environmental contaminants. It also considers alternate uses and functions for antimicrobial compounds other than those intended for medicinal purposes in humans, animals, and fish. Recognizing the connectivity between overlap.
Chapter 23: Effect of Veterinary Medicines Introduced via Manure into Soil on the Abundance and Diversity of Antibiotic Resistance Genes on Their TransferabilityChapter 24: Tracking Antibiotics and Antibiotic Resistance Genes through the Composting Process and Field Distribution of Poultry Waste: Lessons Learned; Chapter 25: Environmental Microbial Communities Living Under Very High Antibiotic Selection Pressure; Chapter 26: Antibiotic Use During an Influenza Pandemic: Downstream Ecological Effects and Antibiotic Resistance.
Chapter 27: Use of Veterinary Antibacterial Agents in Europe and the United States.
Print version record.
Keywords: Antibiotics -- Environmental aspects; Drug resistance in microorganisms; Science; Natural history; Electronic books